(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the evacuation of starving children from the Volga and Ural regions of Russia to the Turkestan ASSR in the 1920s, and the subsequent re-evacuation of the starving children to their homeland. At the same time, the state of implementation of measures taken by the state to evacuate children to our country and the reasons and processes of re-evacuation of children were analyzed on the basis of archival materials and scientific literature. Through the study of relevant sources, issues such as the excessive number of children’s evacuations, the establishment of orphanages and orphanages in our country, as well as the care of our kind and childearing people for hungry children have achieved an objective solution it has been. In conclusion, one can infer that the Soviet authorities carried out the evacuation and re-evacuation measures in a fragmented manner, that is, providing children with housing, food, clothing and the evacuation efforts were unsatisfactory.